2010
DOI: 10.1093/brain/awq021
|View full text |Cite
|
Sign up to set email alerts
|

Early functional magnetic resonance imaging activations predict language outcome after stroke

Abstract: An accurate prediction of system-specific recovery after stroke is essential to provide rehabilitation therapy based on the individual needs. We explored the usefulness of functional magnetic resonance imaging scans from an auditory language comprehension experiment to predict individual language recovery in 21 aphasic stroke patients. Subjects with an at least moderate language impairment received extensive language testing 2 weeks and 6 months after left-hemispheric stroke. A multivariate machine learning te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
83
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(96 citation statements)
references
References 36 publications
11
83
0
2
Order By: Relevance
“…Bilateral SFG activity at the subacute stage was also related to aphasia recovery, consistent with findings of increased subacute activity in frontal regions in previous longitudinal studies on aphasia recovery (Fernandez et al, 2004;Saur et al, 2006;Saur et al, 2010). However, in the present study, we observed a negative correlation between left SFG subacute activity for pseudowords and single word comprehension at the chronic stage.…”
Section: Relationship Between Subacute Brain Activity and Language Resupporting
confidence: 92%
See 3 more Smart Citations
“…Bilateral SFG activity at the subacute stage was also related to aphasia recovery, consistent with findings of increased subacute activity in frontal regions in previous longitudinal studies on aphasia recovery (Fernandez et al, 2004;Saur et al, 2006;Saur et al, 2010). However, in the present study, we observed a negative correlation between left SFG subacute activity for pseudowords and single word comprehension at the chronic stage.…”
Section: Relationship Between Subacute Brain Activity and Language Resupporting
confidence: 92%
“…Nevertheless, the degree of left insula/IFG activity in an individual was related to overall recovery capacity. This finding is in general agreement with the observation that left frontal activity in the subacute stage is associated with improved word comprehension (Heiss et al, 1999) and predictive of global language improvement (Saur et al, 2010).…”
Section: Relationship Between Subacute Brain Activity and Language Resupporting
confidence: 91%
See 2 more Smart Citations
“…For example, Du et al 55 combined both task-and task-free fMRI in schizophrenia in a small study. Additionally, combinations of fMRI measures with volumetric data, 41,[48][49][50]63,76,[78][79][80][81]86,89 DTI, 46,49,92 as well as genetics 42 and behavioral data, 40,41,50,76 have been used as features in MVPA analyses. However, results reported so far do not allow verified statements about the benefit of such multimodal acquisitions.…”
Section: Recent Diagnostic Fmri Approaches Based On Mvpamentioning
confidence: 99%